Proposta metodológica para estimativa de fluxos de carga a partir de dados secundários: uma aplicação em Belo Horizonte - Lilian dos Santos Fontes Pereira (2013)
The freight flow in urban areas is of great importance for economy. However, it brings several negative externalities and is the subject of conflict of interests of different actors. Understanding this complex system is crucial to guide public policies able to establish a balance between the positive and negative aspects of the flow of charge in an urban environment, and is a major challenge of City Logistics. Among the planning tools aiming to enable this understanding, the matrix Origin Destination (OD), is of great relevance. However, traditional methods based on field surveys have a high cost and methodological difficulties of data collection, which often makes it impossible to update the information. This study aims to validate and evaluate the applicability of a methodology proposed to estimate a freight OD matrix from secondary data, employing principles of activity-based models. These models seek to investigate the relationships that cause the need to travel and can be understood in the context of freight transportation, as the relations of production and consumption that generate demand for goods shifts. In this sense, this study presents a methodology composed of seven stages, including the definition of the study area, zoning, choice of the economic segments to be detailed, collection and processing of secondary data, trip generation, trip distribution and modeling for calibration. To validate, the methodology was applied to the city of Belo Horizonte, based on data from the Municipal Register of Taxpayers (CMC) and use the Integrated Land Use and Transportation, activity-based Model, using the software TRANUS. The model results were compared with official data from the municipality and field data collected in previous studies. The methodology proved applicable, consistent and valid results.